Evaluation of natural additives for warm asphalt mix - Herrera de la Rosa, Rosa; Alonso Aenlle, Anadelys; Villegas Muñoz, Nelson (Revista de la Construcción. Journal of Construction, 2018)
Asphalt professionals in Cuba, taking as a line of work the sustainability of pavements, are involved in the methods for obtaining warm asphalt mixtures, as a technology to achieve construction efficiency, conservation of resources and the environment without affecting the mechanical performance of hot asphalt mixes. On this basis, two fundamental lines have been investigated to obtain this type of mixtures, using natural resources of existence in the country: the natural zeolites of the Tasajera deposit and the sugar cane wax. The work exposes the availability of resources, as well as the main results derived from the researches carried out. The temperature reductions obtained from experimental research using both additions of natural origin is between 20-30oC, which allows sustainable results in the production of asphalt mixtures.